Lubrication of metal-on-metal hip joints: The effect of proteincontent and load on film formation and wear - Myant,CW; underwood,R; fan,J; cann,P (Journal of the Mechanical Behavior of Biomedical Materials, 2011)
Lubricant films were measured for a series of bovine serum and protein containing (albumin, globulin) saline solutions for CoCrMo femoral component sliding against a glass disc. Central film thickness was measured by optical interferometry as a function of time (constant mean speed: 0 and 10 mm/s) and variable mean speed (0–50 mm/s). The effect of load (5–20 N) on film thickness was also studied. The development of the wear scar on the CoCrMo surface was monitored by measuring the width of the contact zone during the film thickness tests. The results showed film thickness increased with time for both the static and sliding tests. Films formed in the static, loaded test were typically in the range of 3–40 nm. The globulin containing solutions formed the thickest films. In the sliding tests a wear scar rapidly formed on the implant component for the bovine serum and albumin fluids, negligible wear was observed for the globulin solutions. Film thickness increased with sliding time for all test solutions and was much greater than predicted by isoviscous EHL models. The film increase was found to correlate with increasing wear scar size and thus decreasing contact pressure. A new lubricating mechanism is proposed whereby during sliding the fluid undergoes bulk phase separation rheology, so that an elevated protein phase forms in the inlet zone. This protein phase is a high-viscosity biphasic matrix, which is periodically entrained into the contact forming a thick protective hydro-gel film. One of the main findings of this study is that film thickness was very sensitive to load; to a much greater extent than predicted by EHL models. Thus film formation in MoM hip joints is very susceptible to high contact pressures which might be due to implant misalignment and edge-loading.